2000
DOI: 10.1038/74710
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy of experimental brain tumors using neural progenitor cells

Abstract: Glioblastomas, the most frequent and malignant of primary brain tumors, have a very poor prognosis. Gene therapy of glioblastomas is limited by the short survival of viral vectors and by their difficulty in reaching glioblastoma cells infiltrating the brain parenchyma. Neural stem/progenitor cells can be engineered to produce therapeutic molecules and have the potential to overcome these limitations because they may travel along the white matter, like neoplastic cells, and engraft stably into the brain. Retrov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
308
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(316 citation statements)
references
References 18 publications
3
308
1
3
Order By: Relevance
“…Benedetti and Staflin et al described the ability of nonengineered rat neural progenitors to inhibit glioma growth in vivo. 25,26 The exact mechanism underlying the observations remains unclear, although they have reported that NSCs may elaborate a secretory agent that could inhibit tumor cell growth. For verifying this demonstration, we co-cultured BMSCs and C6 at the ratio of 1:1.…”
Section: Discussionmentioning
confidence: 99%
“…Benedetti and Staflin et al described the ability of nonengineered rat neural progenitors to inhibit glioma growth in vivo. 25,26 The exact mechanism underlying the observations remains unclear, although they have reported that NSCs may elaborate a secretory agent that could inhibit tumor cell growth. For verifying this demonstration, we co-cultured BMSCs and C6 at the ratio of 1:1.…”
Section: Discussionmentioning
confidence: 99%
“…DC injection induced specific T-cell reactivity against 9L, the level of response was rather modest. 26 Cytokine gene therapy for gliomas appears to have a promising future, based on encouraging results in murine models, 19,27 although the efficacy in orthotopic i.c. models remains inferior to that observed in systemic tumor models.…”
Section: Glioma Gene Therapy With Ifn-a and Dcsmentioning
confidence: 99%
“…This gene therapy approach was based on the grafting of neural stem cells (NSC) producing therapeutic molecules. 77 Well-characterized NSC lines (lacZ and/or CD-positive) injected into the tail vein of adult nude mice with established experimental intracranial and/or subcutaneous flank tumors of neural and non-neural origin were localized to various tumor sites with little accumulation in normal tissues. These findings suggested that intravascularly administered NSCs may be an effective delivery vehicle to target invasive tumors of neural and non-neural origin, both within and outside the brain.…”
Section: Stem Cellsmentioning
confidence: 99%